Peningkatan Kemampuan Berpikir Kritis, Kemampuan Pemecahan Masalah dan Minat Belajar Siswa Dengan Board Game di SMA Kristen 1 Tomohon - Rangian, Stevani Caroline; Estafianto, Hary Dwi (Peneliti.net, 2024)
This study aims to determine the relationship between eye-foot coordination This study aims to determine: 1) the results of developing the board game